Analytically determining the abrasive wear of materials - Вишневський, О.А. (Proceedings of National Aviation University (archive), 2007)
The criterion of abrasive wear resistance of materials concerning average pressure upon the friction surface during all experiment is defined.Dependence of a linear wear intensity on pressure is established.